Preoperative Assessment of Anxiety and Depression Using Computerized Adaptive Screening Tools: A Pilot Prospective Cohort Study. (27th December 2021) - Bass, Victoria; Brown, Frank; Beiser, David G.; Peterson, Tarren; Gibbons, Robert D.; Nagele, Peter
Abstract : BACKGROUND: Serious mental health conditions (eg, anxiety and depression) are common in surgical patients, yet likely underassessed due to the time-consuming and cumbersome traditional screening process. A recently developed computerized adaptive mental health assessment tool (computerized adaptive test-mental health [CAT-MH]) allows rapid, precise, and accurate assessment of numerous mental health disorders, including anxiety and depression, without the need for a trained interviewer. The goal of this investigation was to determine the feasibility of administering CAT-MH for anxiety and depression in the preoperative setting and to obtain preliminary evidence of the prevalence of anxiety and depression in preoperative patients. METHODS: In this prospective cohort study, 100 adult patients scheduled for elective surgery were enrolled and asked to complete the CAT-MH in the preoperative clinic. Urgent and emergency surgeries were excluded as were pregnant patients. Primary feasibility outcomes were completion rate and time to completion. Secondary outcomes were prevalence estimates of anxiety and depression. RESULTS: All 100 enrolled patients completed the study. All patients were able to complete the mental health assessment (mean time: 3.6 ± 1.8 minutes standard deviation). Sixteen patients (16%) screened positive for anxiety (severity: mild, n = 7 [7%]; moderate, n = 7 [7%]); severe, n = 2 [2%]); 12 of 16 (75%) did not have a previous diagnosis of anxiety disorder. Twenty-eight (28%) patients screened positive for depression (severity: mild, n = 26 [26%]; moderate and severe, n = 1 each [1%]); 23 of 28 (82%) had no previous diagnosis of depressive disorder. Nineteen patients (19%) met the screening criteria for major depressive disorder; 14 of 19 (74%) of which had no previous diagnosis of major depressive disorder. CONCLUSIONS: The results of this pilot study support the feasibility of using CAT-MH in a preoperative evaluation and indicate that there is a substantial prevalence of undiagnosed anxiety and depression in surgical patients.